El Excentrico, 1972-01-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
January 5, 1972 [5 de enero de 1972]. No volume or issue number. Cover has a photograph of a dove and the headline says "Peace and Happiness 1972." There is also photograph of Mr. Guerrero to advertise his immigration and income tax services.